Effect of azf region microdeletion on y chromosome forensic markers (2015)
Subject and scope: The aim of this review is to share the studies that have beenconducted in the world on y chromosome microdeletions and their possible effects on the observed genetic-forensic results. Features: y chromosome infertility is usually caused by deletions of genetic material in areas related to the azoospermia factor (azf) located in three contiguous regions of yq: azfa, azfb and azfc. Findings: There is evidence that some of the str routinely used in the forensic genetics laboratory with multiplex kits are located in these regions, which allows to detect the existence of microdeletions in some loci. Increasing awareness of the microstructural events inside the y chromosome can be useful for a better characterization of abnormal repetitive patterns complicating the interpretation of dna profile. Conclusions: Variation in population studies on prevalence of microdeletions may be due to differences in patient screening, sample size and technique used. Reported cases conclude that the loci generally affected are dys385 and dys392, indicating microdeletions in the azfb region, and that dys448 is related to microdeletions in the azfc region.